PENERAPAN METODE K - MEANS CLUSTERING DALAM MEMPREDIKSI TINGKAT PEMINAT EKSTRAKURIKULER PADA SISWA SMA MUHAMMADIYAH 4 BENGKULU - Elsi Apri Yanti; Dewi Suranti; Devi Sartika (Smart Education, 2024)
Abstract: Extracurricular activities are additional activities carried out outside of class hours which are carried out either at school or outside school with the aim of gaining additional knowledge, skills and insights and helping to shape the character of students according to their respective interests and talents. The extracurricular activities at SMA Muhammadiyah 4 Bengkulu include 4 extracurricular activities, namely soccer, volleyball, futsal, and scouts. K-Means is one of the data mining methods that is without direction, meaning that this method is applied without training and without a teacher and does not require an output target. The system development method used is Waterfall, K-Means Clustering. The application of the implementation of the K-Means Clustering method in predicting the level of interest in extracurricular activities at SMA Muhammadiyah 4 Bengkulu students was built using the Visual Basic.Net 2010 programming language with the Ms.Access database. From the results of the implementation and testing of the application, it shows that the application can provide recommendations for clustering students' interests and talents for extracurricular activities at SMA 4 Muhammadiyah 4 of Bengkulu City which are input into the application properly. Keywords: data mining, k-means, clustering, extracurricular activities Abstrak: Kegiatan ekstrakurikuler atau ekskul adalah kegiatan tambahan yang dilakukan di luar jam pelajaran yang dilakukan baik di sekolah atau di luar sekolah dengan tujuan untuk mendapatkan tambahan pengetahuan, keterampilan dan wawasan serta membantu membentuk karakter peserta didik sesuai dengan minat dan bakat masing. Adapun Kegiatan ekstrakurikuler di sekolah SMA Muhammadiyah 4 Bengkulu meliputi 4 ekstrakurikuler yaitu Sepak bola, Bola Voli, Futsal, dan Pramuka. K-Means merupakan salah satu metode data mining yang bersifat tanpa arahan, maksudnya metode ini diterapkan tanpa adanya latihan dan tanpa ada guru serta tidak memerlukan target output. Metode pengembangan sistem yang digunakan adalah Waterfall, K-Means Clustering . Aplikasi implementasi metode K-Means Clustering Dalam Memprediksi Tingkat Peminat Kegiatan Ekstrakurikuler Pada Siswa SMA Muhammadiyah 4 Bengkulu dibangun dengan menggunakan bahasa pemrograman Visual Basic.Net 2010 dengan database Ms.Access. Dari hasil implementasi dan pengujian dari aplikasi menunjukkan bahwa aplikasi dapat memberikan rekomendasi clustering minat dan bakat siswa terhadap kegiatan ekstrakurikuler di SMA 4 Muhammadiyah 4 Kota Bengkulu yang di – input ke dalam aplikasi dengan baiki. Kata kunci: data mining, k-means, clustering, ekstrakurikuler